Potencial das biomassas disponíveis no nordeste brasileiro como fontes alternativas de geração de energia - Machado, Ana Mercedes Corrêa (2010)
The global warming caused by emission of greenhouse gases, especially CO2 (carbon dioxide) comes from fossil fuels and the destruction of forests through deforestation and burning, has generated major changes in the environment, getting to interfere with natural phenomena. Alternative energy and less polluting sources have been identified as one of the solutions to mitigate the problem. Brazil, to meet the commitment made in Kyoto Protocol and has advanced technology to produce ethanol from sugar cane, has increased its acreage, often replacing traditional cultures, in order to maintain the leadership in the international market. The present study aimed to point out other possible raw materials for production of ethanol in the Northeast region s biodiversity, particularly in Sergipe, with the utilization of waste and underexploited biomass in order to add value, while the folk traditions, as an alternative development for the region within the principles of sustainability. In Sergipe, estimated the potential for ethanol production from cassava wastewater, waste generated in the processing of cassava flourmills in the city of Campo do Brito, we determinated the number of possible micro-distilleries to be operating; verified the production possibility in a 10 years period. It was studied the potential to get ethanol from the waste of sisal fiber came from the most producers municipalities in the State of Bahia, where determinated the number of possible micro-distilleries and economic feasibility. It was estimated the production potential of ethanol from mesquite and the capability to roll out micro-distilleries in the Northeast. According to the results, was found the feasibility of ethanol production from these biomasses available in the Northeast as an alternative source of cleaner energy.